SOCIO-ECONOMIC ANALYSIS OF UBER TAXI DRIVERS IN KERALA - A STUDY WITH SPECIAL REFERENCE TO ERNAKULAM DISTRICT - Shoja Rani, B.N (Shanlax International Journal of Economics, 2018)
We are living in the times where many transactions are done and requirements met online like in the sectors of banking, shopping, advertisement, etc. Among these, of great influence is the use of taxi service done online. With the help of smartphones, arranging and using cab service has become easy and cheap. One of the most popular brands in the sector is Uber. Due to its convenience, many users opt for it than the taxi service available at the conventional taxi stand even when there are vehicles available in abundance. It is highly surprising to note that even when Uber has a wide network across the globe, they do not own even a single car. All this is possible by the use of a location-based app (software) capable of linking the drivers and the users efficiently, which also brings down the cost of travel. The network of users and drivers along with geographical location made available through GPS make it easy for the user to locate the nearest taxi available to take him efficiently even through heavy traffic to his destination. The present article focuses on the socio-economic conditions of the drivers, the problems faced by the drivers and the users, customer satisfaction, etc.